2022
DOI: 10.3389/fvets.2022.879630
|View full text |Cite
|
Sign up to set email alerts
|

Role of Animal Models to Advance Research of Bacterial Osteomyelitis

Abstract: Osteomyelitis is an inflammatory bone disease typically caused by infectious microorganisms, often bacteria, which causes progressive bone destruction and loss. The most common bacteria associated with chronic osteomyelitis is Staphylococcus aureus. The incidence of osteomyelitis in the United States is estimated to be upwards of 50,000 cases annually and places a significant burden upon the healthcare system. There are three general categories of osteomyelitis: hematogenous; secondary to spread from a contigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 171 publications
0
11
0
1
Order By: Relevance
“…A secondary benefit of this model was the ability to investigate initial clearance of ST398 via local antimicrobial-laden implant placement. This model, based upon previously published literature ( Sodnom-Ish et al, 2021 ), and fulfilling the main tenants of an animal model of osteomyelitis ( Billings and Anderson, 2022 ), had a success rate of 50% in rats inoculated with SA but not treated with any antibiotic and 20% of rats challenged with SA and a low dose of antibiotic. Success was defined as clinical osteomyelitis lesions and positive SA recovery.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A secondary benefit of this model was the ability to investigate initial clearance of ST398 via local antimicrobial-laden implant placement. This model, based upon previously published literature ( Sodnom-Ish et al, 2021 ), and fulfilling the main tenants of an animal model of osteomyelitis ( Billings and Anderson, 2022 ), had a success rate of 50% in rats inoculated with SA but not treated with any antibiotic and 20% of rats challenged with SA and a low dose of antibiotic. Success was defined as clinical osteomyelitis lesions and positive SA recovery.…”
Section: Discussionmentioning
confidence: 96%
“…This may include an in vivo dose curve of ST398 in comparison to a more widely characterized sequence type, such as USA300 or UAMS1 to add clarity regarding the interspecies potential of ST398 to establish osteomyelitis. It is suggested that this occur either in rats or rabbits, as rabbits are well-suited to dose-curves and pathogenesis investigation ( Billings and Anderson, 2022 ). Once established, there may be value in investigating for intracellular bacteria from harvested bone, whether that is through TEM or in vivo monitoring techniques to evaluate viability of bone cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Рост числа высокоэнергетических травм в гражданских условиях, а также в условиях боевых действий, ведет к росту числа случаев использования металлических имплантатов в ортопедо-травматологической практике [1]. Одним из наиболее опасных осложнений, связанных с хирургической установкой ортопедических устройств (устройства для фиксации переломов, протезы суставов), является остеомиелит, который вызывается инфекционными микроорганизмами и приводит к прогрессирующему разрушению и потере костной ткани [2]. Несмотря на совершенствование технологий лечения, количество таких осложнений продолжает неуклонно расти [3; 4], что требует дальнейшей разработки эффективных способов профилактики и ликвидации остеомиелитического процесса.…”
unclassified